2009
DOI: 10.1111/j.1476-5381.2009.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct molecular requirements for activation or stabilization of soluble guanylyl cyclase upon haem oxidation‐induced degradation

Abstract: Background and purpose:In endothelial dysfunction, signalling by nitric oxide (NO) is impaired because of the oxidation and subsequent loss of the soluble guanylyl cyclase (sGC) haem. The sGC activator 4-[((4-carboxybutyl){2- [(4-phenethylbenzyl) oxy]phenethyl}amino)methyl[benzoic]acid (BAY 58-2667) is a haem-mimetic able to bind with high affinity to sGC when the native haem (the NO binding site) is removed and it also protects sGC from ubiquitin-triggered degradation. Here we investigate whether this prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
36
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 48 publications
8
36
1
Order By: Relevance
“…Previous studies indicated that oxidation-induced degradation becomes prominent when the incubation time exceeds 2 h [11], [32]. Therefore, washed platelets were incubated with ODQ (10 µM) in the absence and in the presence of BAY 60-2770 (10 µM) for 2.5 h, after which levels of sGC protein for α1 and β1 sGC subunits were determined.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that oxidation-induced degradation becomes prominent when the incubation time exceeds 2 h [11], [32]. Therefore, washed platelets were incubated with ODQ (10 µM) in the absence and in the presence of BAY 60-2770 (10 µM) for 2.5 h, after which levels of sGC protein for α1 and β1 sGC subunits were determined.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been demonstrated that sGC with oxidized heme has a propensity to lose the heme moiety [11, 12]. The pool of ferric or heme-free sGC is much more susceptible to degradation [12, 13]. About fifteen years ago, NO-independent sGC activators and stimulators were discovered [14, 15]; these agents enhance sGC activity in a heme-dependent or -independent manner.…”
Section: Introductionmentioning
confidence: 99%
“…20 It activates oxidized/heme-free sGC by binding in the sGC heme pocket and mimicking the heme group; it also protects heme-free sGC from oxidation-induced proteasomal degradation. Cinaciguat therefore opens up the possibility of new mechanism-based therapies for cardiovascular diseases associated with oxidative stress, 8,23 and is currently in clinical development for the treatment of acute decompensated heart failure. 24–26 A more recently discovered sGC activator, the anthranilic acid derivative ataciguat (HMR 1766), 27 has also been studied in clinical trials in healthy volunteers, 28 in patients with intermittent claudication due to peripheral arterial disease and in patients with neuropathic pain.…”
mentioning
confidence: 99%